HUMANS AS INDIVIDUAL AND SOCIAL BEINGS IN EVERYDAY LIFE - Artha Sari, Diah; Pasaribu, Rini Azhari (International Journal of Students Education, 2023)
In everyday life, apart from being an individual person, he is also a social being who really needs the help of others. a person cannot live his own life even to achieve his needs, humans need other people to help them. Every human being in society needs to communicate, socialize and interact with others. Humans are social creatures since birth, humans who will be born also need the help of others to provide help. In principle, all life cannot be separated from the influence of interaction, socialization and communication. Communication is very important because through communication, a person can express what he wants and expects from others in his actions.